The Influence of Work Environment and Satisfaction on Employee Performance at Bank PT. BPR BKK BLORA Jepon Branch - Desintaputri, Riska Amalia; Harsono, Harsono (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of work environment and job satisfaction on employee performance at Bank PT BPR BKK Blora Jepon Branch. In the increasingly competitive banking world, a conducive work environment and a high level of job satisfaction are important factors in increasing employee productivity and effectiveness. This study uses a quantitative approach with a survey method on 116 respondents who are employees of BPR BKK Blora. Data were collected using a questionnaire with a Likert scale, then analyzed using multiple linear regression through the t test and F test. The results of the study indicate that partially, the work environment has a positive and significant effect on employee performance with a significance value of 0.033 < 0.05. Conversely, job satisfaction does not have a significant effect on employee performance with a significance value of 0.464 > 0.05. Simultaneously, both variables also do not have a significant effect on employee performance (sig. 0.063 > 0.05). These findings indicate that improving employee performance is not only influenced by the environment and job satisfaction, but also by other factors such as motivation, leadership style, and individual competence.